1997
DOI: 10.1136/jech.51.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Use of paracetamol for suicide and non-fatal poisoning in the UK and France: are restrictions on availability justified?

Abstract: It has been suggested that making the means of suicide less accessible to patients may result in reductions in method specific suicide rates and in overall suicides.89 In this paper we examine trends in paracetamol poisoning in countries where the availability of paracetamol differs -England and Wales and in France. In England and Wales paracetamol is freely available in unlimited quantities from chemists and up to 12 g may be purchased from supermarkets. In France paracetamol may only be purchased from pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 17 publications
2
104
0
7
Order By: Relevance
“…Legislative changes in the United Kingdom leading to restrictions in the sales of acetaminophen have reduced the number of patients dying from or needing transplantation because of acetaminophen hepatotoxicity. 33,[41][42][43][44][45][46] Because most cases in the United Kingdom are considered to be suicidal, they differ in that sense from unintentional cases. Nevertheless, efforts to limit OTC package size and to restrict the prescription of narcotic-acetaminophen combinations (or to separate the narcotic from the acetaminophen) may be necessary to reduce the incidence of this increasingly recognized but preventable cause of ALF in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Legislative changes in the United Kingdom leading to restrictions in the sales of acetaminophen have reduced the number of patients dying from or needing transplantation because of acetaminophen hepatotoxicity. 33,[41][42][43][44][45][46] Because most cases in the United Kingdom are considered to be suicidal, they differ in that sense from unintentional cases. Nevertheless, efforts to limit OTC package size and to restrict the prescription of narcotic-acetaminophen combinations (or to separate the narcotic from the acetaminophen) may be necessary to reduce the incidence of this increasingly recognized but preventable cause of ALF in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…4 France, a country that has some restrictions on paracetamol sales, sees comparatively fewer cases, though numbers may have increased in conjunction with an overall increase in sales. 5 Australia has reported that over 30% of cases seen at major transplant centers are due to this product as well. 6 The experience from Spain stands out as unique among characterized Western populations.…”
Section: See Article On Page 1389mentioning
confidence: 99%
“…Both France and the United Kingdom have found that limited package size and restriction of amounts purchased has correlated with fewer paracetamol-related deaths. 5,9 An Irish study found that 30% of nonfatal overdoses in that country involved paracetamol, and that survivors reported relative ease of access as a principal reason for choosing that compound. 10 Paracetamol overdoses are reportedly common in Sweden as well, 11 and the list goes on.…”
Section: See Article On Page 1389mentioning
confidence: 99%
“…[1] Paracetamol overdose is a common means of self-poisoning worldwide due its wide availability and accessibility. [2] It is widely available as a single-component medication and also as a component of a plethora of combination over-the-counter and prescription medications. Despite its safety when used properly, Paracetamol poisoning is one of the more common overdoses reported to poison centers.…”
Section: Introductionmentioning
confidence: 99%